2003
DOI: 10.1093/annonc/mdg064
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological treatment of aggressive fibromatosis: a systematic review

Abstract: The evidence in the literature supports the opinion that both non-cytotoxic and cytotoxic chemotherapies are effective against AF. However, the lack of sufficient patient numbers and randomized trials compromises the validity of the reported results and mandates further investigation with properly designed prospective studies including larger patient numbers, with main end points to include not only tumor response rate and survival but also quality-of-life issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
201
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(211 citation statements)
references
References 70 publications
1
201
1
7
Order By: Relevance
“…3 It has been suggested that the presence of antiestrogen binding sites distinct from ER play a role in treatment with antiestrogens in adult AF. 18 In two studies, including the current analysis, four tested children with AF did not express ER. 17 The role of ER expression and antiestrogen binding sites in the pathogenesis of childhood AF and options for treatment have yet to be established.…”
Section: Discussionmentioning
confidence: 91%
“…3 It has been suggested that the presence of antiestrogen binding sites distinct from ER play a role in treatment with antiestrogens in adult AF. 18 In two studies, including the current analysis, four tested children with AF did not express ER. 17 The role of ER expression and antiestrogen binding sites in the pathogenesis of childhood AF and options for treatment have yet to be established.…”
Section: Discussionmentioning
confidence: 91%
“…The systemic therapy commonly used is the antiestrogen Tamoxifen, which causes inhibition of ER beta expression. It is found to cause partial response to the tumour or stabilizes disease process and prevents progression [9]. In addition to Tamoxifen, high dose Sulindac has also been used as it inhibits beta catenin signaling and has been found to have additive effect to Tamoxifen [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…It is found to cause partial response to the tumour or stabilizes disease process and prevents progression [9]. In addition to Tamoxifen, high dose Sulindac has also been used as it inhibits beta catenin signaling and has been found to have additive effect to Tamoxifen [9,10]. A combination of vincristine, actinomycin D and cyclophosphamide has also been used in few selective cases not responding to hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Possible candidates for systemic therapy include patients with Gardner's syndrome and unresectable or recurrent desmoid tumors, involving the mesentery [15]. It must be emphasized that, to date, the evidence regarding the efficacy of these agents are drawn from case reports and single-arm series with small patient numbers [16]. …”
Section: Discussionmentioning
confidence: 99%